Mini Review: Correlations of Cognitive Domains With Cerebrospinal Fluid α-Synuclein Levels in Patients With Parkinson's Disease - Murakami, Hidetomo; Ono, Kenjiro; Shiraishi, Tomotaka; Umehara, Tadashi; Omoto, Shusaku; Iguchi, Yasuyuki (Frontiers in Aging Neuroscience, 2021)
The level of α-synuclein, a component of Lewy bodies, in cerebrospinal fluid (CSF) in Parkinson’s disease (PD) has attracted recent attention. Most meta-analyses conclude that CSF levels of α-synuclein are decreased in PD. Patients with PD present with cognitive impairment, including frontal/executive dysfunction in the early phase and later emergence of visuospatial and mnemonic deficits. To examine whether CSF α-synuclein levels reflect the activities of various cognitive domains, we reviewed reports examining the association of these levels with cognitive performance in each domain in PD. Among 13 cross-sectional studies, five showed that a lower CSF α-synuclein level was associated with worse cognitive function. In four of these five reports, frontal/executive function showed this association, suggesting a link of the pathophysiology with Lewy bodies. In three other reports, a higher CSF α-synuclein level was associated with temporal-parieto-occipital cognitive deterioration such as memory. In the other five reports, the CSF α-synuclein level did not correlate with cognitive performance for any domain. In four longitudinal studies, a higher baseline CSF α-synuclein level was associated with a worse cognitive outcome, including cognitive processing speed, visuospatial function and memory in two, but not with any cognitive outcome in the other two. The different associations may reflect the heterogeneous pathophysiology in PD, including different pathogenic proteins, neurotransmitters. Thus, more studies of the association between cognitive domains and CSF levels of pathogenic proteins are warranted.